FGF23 beyond Phosphotropic Hormone. (November 2018) - Takashi, Yuichi; Fukumoto, Seiji
Abstract : Fibroblast growth factor (FGF) 23 is a bone-derived phosphotropic hormone that regulates phosphate and vitamin D metabolism. FGF23 mainly affects kidney function via the FGF receptor (FGFR)/α-Klotho complex. The physiological roles of FGF23 and α-Klotho in the regulation of mineral homeostasis have been well established. In addition, recent studies have reported that FGF23 has various effects on many other tissues, sometimes in an α-Klotho-independent manner, especially under pathological conditions. However, how FGF23 works in these tissues without α-Klotho is not entirely clear. Here we review the recent reports concerning the actions of FGF23 on various tissues and discuss the remaining questions about FGF23. Highlights: It is well established that FGF23 is a phosphotropic hormone produced by bone and is essential for maintaining phosphate metabolism. In addition, FGF23 was reported to have many other functions, especially under pathological conditions such as CKD with high circulatory FGF23 levels. FGF23 was reported to cause LVH, vascular calcification, impaired neutrophil activation, enhanced production of inflammatory cytokines from liver, and decreased erythropoiesis via the activation of several FGFRs (i.e., FGFR1, 2, 4) in both an α-Klotho dependent and independent manner. Several modulators of FGF23 production, such as iron deficiency, hypoxia, aldosterone, and insulin signaling, have been reported. The significance of these actions and modulators of FGF23 has not yet been established, especially in humans.